Marketing Plan for Company X - Kathleen Kwarso (iBuss Management, 2017)
In the globalization era where competition is tighter than ever, creating a sustainable and customized marketing strategy that would withstand the fast shift in trends is of utmost importance. Unfortunately, many B2B businesses are still underestimating innovative B2C channels, which leads to the late adoption of marketing trend. Company X is also experiencing this problem where they are too dependent on clients’ loyalty. Therefore, the purpose of this paper is to create a tailored and innovative marketing plan for Company X. Qualitative method will be utilized by interviewing internal and external parties related with Company X. The findings show that creating a consumer-centric company supported with the multichannel model will be beneficial in increasing awareness, exposure and even sales of Company X. Keywords:Service Marketing Mix, Marketing Channel, Market Research, Multichannel, Consumer-Centric